Computed tomographic visualisation and 2D/3D microscopic evaluation of soil macro- and micromorphology - Pospíšilová, Ľubica; Plíšková, Jana; Jaques, Victory; Zikmund, Tomáš; Sedlák, Luboš; Eichmeier, Aleš; Klement, Aleš; Kodešová, Radka; Borůvka, Luboš; Kaiser, Jozef; Menšík, Ladislav (CZECH ACADEMY AGRICULTURAL SCIENCES, 2024)
Soil organic matter and pores distribution within aggregates were studied using X-ray computed tomography (XCT; Nikon XT H 225ST and GE Phoenix L240) and advanced 2D/3D measurements by the digital Keyence VHX-6000 microscope (Japan). A new methodological approach with computed tomography involvement for studying the spatial arrangement of pores, porosity, and soil morphology is presented. Changes in studied parameters are documented along the transect of intensively used Haplic Chernozem. Soil disturbance due to erosion and colluvial soil profile formation is reported. Moreover, soil organic matter quality and aggregate stability were evaluated. Obtained results showed statistically significant differences between the control and eroded sites and between eroded and accumulated sites. The correlation coefficients were the highest for soil organic carbon (SOC) and humic substances C-HS (r = 0.805) and C-HS and C-HA/C-FA (r = 0.764). The highest porosity, aggregates stability and coefficients stability were confirmed on the eroded site. The computed tomography measurements also document the high disturbance of Haplic Chernozem on the control site and the newly formed profile of Colluvisol. Despite excellent complementary technique further research is necessary to improve micro-XCT resolution and capacity for the soil micromorphological study.

Soil organic matter and pores distribution within aggregates were studied using X-ray computed tomography (XCT; Nikon XT H 225ST and GE Phoenix L240) and advanced 2D/3D measurements by the digital Keyence VHX-6000 microscope (Japan). A new methodological approach with computed tomography involvement for studying the spatial arrangement of pores, porosity, and soil morphology is presented. Changes in studied parameters are documented along the transect of intensively used Haplic Chernozem. Soil disturbance due to erosion and colluvial soil profile formation is reported. Moreover, soil organic matter quality and aggregate stability were evaluated. Obtained results showed statistically significant differences between the control and eroded sites and between eroded and accumulated sites. The correlation coefficients were the highest for soil organic carbon (SOC) and humic substances C-HS (r = 0.805) and C-HS and C-HA/C-FA (r = 0.764). The highest porosity, aggregates stability and coefficients stability were confirmed on the eroded site. The computed tomography measurements also document the high disturbance of Haplic Chernozem on the control site and the newly formed profile of Colluvisol. Despite excellent complementary technique further research is necessary to improve micro-XCT resolution and capacity for the soil micromorphological study.
Computed tomographic visualisation and 2D/3D microscopic evaluation of soil macro- and micromorphology
Keywords: aggregate stability; porosity; soil organic matter; X-ray computed tomography; aggregate stability; porosity; soil organic matter; X-ray computed tomography